HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA TANGAN DENGAN HASIL AKURASI SMASH CLUB BOLA VOLI PUTRA SMK MUHAMADIYAH 3 PEKANBARU - Hendrif Padilta; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study was to determine the relationship of limbmuscle power and wrist coordination with accuracy results smash men's volleyball clubSMK Muhammadiyah 3 Pekanbaru. The type of study is a correlation study types. Thisstudy is a correlational study by comparing the measurement results of two differentvariables in order to determine the degree of association between these variables. Thepopulation in this study were as many as 17 samples. Data collection techniques in thisstudy using total sampling for counting a sample that is not too large. Results ofanalysis showed that there is a relationship limb muscle power and wrist coordinationwith accuracy results smash men's volleyball club SMK Muhammadiyah 3 Pekanbaruwith r = (0.819)> rtabel = (0.497).Keywords: Leg Muscle Power, Wrist Coordination, Volleyball Smash